Differential activation and functional specialization of miR-146 and miR-155 in innate immune sensing - Schulte, Leon N. (Oxford University Press, 2013)
Many microRNAs (miRNAs) are co-regulated during the same physiological process but the underlying cellular logic is often little understood. The conserved, immunomodulatory miRNAs miR-146 and miR-155, for instance, are co-induced in many cell types in response to microbial lipopolysaccharide (LPS) to feedback-repress LPS signalling through Toll-like receptor TLR4. Here, we report that these seemingly co-induced regulatory RNAs dramatically differ in their induction behaviour under various stimuli strengths and act non-redundantly through functional specialization; although miR-146 expression saturates at sub-inflammatory doses of LPS that do not trigger the messengers of inflammation markers, miR-155 remains tightly associated with the pro-inflammatory transcriptional programmes. Consequently, we found that both miRNAs control distinct mRNA target profiles; although miR-146 targets the messengers of LPS signal transduction components and thus downregulates cellular LPS sensitivity, miR-155 targets the mRNAs of genes pervasively involved in pro-inflammatory transcriptional programmes. Thus, miR-155 acts as a broad limiter of pro-inflammatory gene expression once the miR-146 dependent barrier to LPS triggered inflammation has been breached. Importantly, we also report alternative miR-155 activation by the sensing of bacterial peptidoglycan through cytoplasmic NOD-like receptor, NOD2. We predict that dose-dependent responses to environmental stimuli may involve functional specialization of seemingly co-induced miRNAs in other cellular circuitries as well.